The Students’ Voices on Lecturers’ Instructional Communication Strategies in EFL Class - Nurdevi Bte Abdul; Nunung Anugrawati; Ummi Khaerati Syam (Celebes Journal of Language Studies, 2021)
This paper is concerned with communication that occurs in the classroom. It aimed at investigating students’ responses on lecturers’ instructional strategies in EFL class. Instructional communication is a field of study that certainly is essential to teachers of speech communication. It focuses on communication variables that can affect any instructional situation, classroom context, or school environment, it is of value to teachers of any subject matter in any discipline as well as to those such as parents who are not teachers by profession but who do engage in instruction periodically. This research used qualitative research method with a case study design. This research was conducted in natural setting. This study was conducted at the campus of state and private universities in South Sulawesi, namely State University of Makassar and Muhammadiyah University of Makassar. There were six lecturers involved in this research from two different universities, and 20 students. Two kinds of instruments were used in collecting data namely observation and interview. In interpretation, it followed Discourse Analysis approach to present the data in extract form. The results the lecturers applied nine strategies to keep the students active the class. Those instructional strategies are using code – switchig, grouping, the use of Information and Communication Technology, feedback, walking arround, humor insertion, question-answer, and scoring system. It can stated that most of students gave positive responses on lecturers’ instructional communication strategies in EFL classroom. They revealed that the strategies applied helped them to actively participate in the classroom.